2012
DOI: 10.3354/dao02420
|View full text |Cite
|
Sign up to set email alerts
|

Fast quantitative PCR, locked nucleic acid probes and reduced volume reactions are effective tools for detecting Batrachochytrium dendrobatidis DNA

Abstract: The fungal pathogen Batrachochytrium dendrobatidis threatens amphibian populations around the world. The ability to detect this pathogen on infected animals and in the environment is critical for understanding and controlling this pandemic. We tested several advances in quantitative PCR (qPCR) techniques to detect B. dendrobatidis DNA. We used a fast PCR thermocycler and enzymes that reduced the volume and the duration of the reaction. We also compared a conventional TaqMan minor groove binding (MGB) probe to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
12
0
8
Order By: Relevance
“…Previous work has shown that fast qPCR can be used to detect Bd, but no sample for sample comparison had yet been done (Ruthig & DeRidder ). This study shows a close approximation of zoospore counts between fast and standard methods (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that fast qPCR can be used to detect Bd, but no sample for sample comparison had yet been done (Ruthig & DeRidder ). This study shows a close approximation of zoospore counts between fast and standard methods (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One study on HIV (Yoder & Fishel 2008) found comparable results between the two methodologies while another study on Epstein-Barr virus (Hilscher, Vahrson & Dittmer 2005) exhibited a significantly lower performance when utilizing fast qPCR. A recent study has shown that fast qPCR can detect Bd (Ruthig & DeRidder 2012), but they did not compare the results directly to the standard method. Therefore, there is a strong need to examine the fast qPCR technique for its effectiveness at quantifying Bd.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini sesuai dengan pendapat (Moleong, 2017) yang menyatakan bahwa untuk menjaring informasi secara luas dari berbagai sumber dan akan menjadi dasar dari rancangan atau teori yang muncul merupakan tujuan dari pengambilan sampel yang diberi batasan. Subjek dipilih berdasarkan kemampuan tinggi, sedang dan rendah sebagai pembaharuan dari penelitian sebelumnya yang bertujuan untuk membandingkan pencapaian dan hambatan kemampuan komunikasi matematis pada masing-masing tingkat kemampuan.Teknik analisis data yang digunakan di dalam penelitian ini adalah analisis sebelum di lapangan dan analisis selama di lapangan Model Miles dan Huberman, yaitu reduksi data, penyajian data dan kesimpulan (Sugiyono, 2014).…”
Section: Metodeunclassified
“…Recent advances in quantitative PCR (e.g. Boyle et al 2004Kirshtein et al 2007, Walker et al 2007, Ruthig & DeRidder 2012 have made detecting and counting microbes easier. Knowing colonization and shedding rates of potential host species in a community would allow researchers to estimate the risk of infection for focal host species.…”
Section: Q U E R C U S a L B A L E A F L I T H O B A T E S C A T E S mentioning
confidence: 99%